2000
DOI: 10.3354/meps193157
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic condition, buoyancy change and mortality in larval cod Gadus morhua. A bioassay for assessing near-term mortality

Abstract: In larvae ot marine fish, density differences are known to be associated with nutritional state and osmotic failure We hypothesized that these density measures can be used to predict the nearterm mortal~ty of larvae. Specifically, we predicted increased larval mortality to be positively and continuously associated with increased larval density. Under controlled conditions, we measured (1) the average density (g cm'3) and daily percent mortality of fed and starved larval cod Cadus morhua L, in culture tanks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In cod, buoyancy is a good indicator of larval condition. Sclafani et al (2000) found a positive linear relationship between larval density and mortality in this species. Some proposed strategies employed by larvae to maintain optimum vertical positioning within the water column are density changes via osmoregulation (Sclafani et al 1997) and synthesis or breakdown of lipids (Guisande et al 1998), which appear to enhance buoyancy in marine fish (Hagen et al 2000;Nursall 1989).…”
Section: Discussionmentioning
confidence: 55%
“…In cod, buoyancy is a good indicator of larval condition. Sclafani et al (2000) found a positive linear relationship between larval density and mortality in this species. Some proposed strategies employed by larvae to maintain optimum vertical positioning within the water column are density changes via osmoregulation (Sclafani et al 1997) and synthesis or breakdown of lipids (Guisande et al 1998), which appear to enhance buoyancy in marine fish (Hagen et al 2000;Nursall 1989).…”
Section: Discussionmentioning
confidence: 55%
“…Moribund eggs and larvae will thus sink, as has been reported for a number of fish species (Blaxter and Ehrlich 1974;Coombs 1981;Yin and Blaxter 1987). As noted by Sclafani et al (2000) in larval cod, increases in larval density resulting from osmotic compromise overwhelm any changes resulting from nutritional effects. These authors determined a critical density for larval cod of 1.0338 g cm -3 , above which there is a [50% probability of dying within 24 h. We observed sinking of Pleuragramma embryonated eggs at temperatures between -1 and 6.5°C under which conditions hatching still took place and the larvae actively swam away from the surface.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have also demonstrated paternal effects on larval and juvenile survival/traits in marine fish (Butts and Litvak, ,b) Because there were equal numbers of larvae in each beaker, density‐dependent mortality rates as mentioned in Sclafani et al. (), can be excluded.…”
Section: Discussionmentioning
confidence: 99%